Rethinking the Sovereignty Principle: Is it a Legal Provision or a Political Domain Nowadays? - Dewi Nurvianti,; Aris Irawan,; Fathurrahman,; Sri Fridayanti, (Indonesia Law Reform Journal, 2023)
The relation of international community currently emphasize that soveregnty princple could not more decide as the main principle in managing a territory of state, even though sovereignty is the main requirement for a state to enforce its law and to do cooperation among entities in international relations. In order to find out the exact interpretation of sovereginty principle, this article used qualitative method. This study find out that sovereignty is recognized as one of the principles in recognizing a state. This term has a political nuance, because the aspect of recognition itself is not a legal aspect but a political one. Moreover, in several cases, even though a country had proclaimed its sovereignty, there are still opportunities for a part of the territory to become independent or even to be acquired by other countries. Thus, it seems that the principle of sovereignty has a tendency as part of politics. However, the principle of sovereignty remains a legal principle based on the provisions of international law, where each country has exclusive rights in every part of its territory, namely in land, air and sea. Currently, the concept of international law has expanded to the politic of international law study, which numerous aspects of law enforcement mingle with a country's policies that are synonymous with political aspects. Additionally, that the current principle of sovereignty should be completed with another legal principle in international law. Abstrak Hubungan masyarakat internasional saat ini menekankan bahwa prinsip kedaulatan tidak dapat lagi diputuskan sebagai prinsip utama dalam pengelolaan suatu wilayah negara, padahal kedaulatan merupakan syarat utama bagi suatu negara untuk menegakkan hukumnya dan untuk melakukan kerjasama antar entitas dalam hubungan internasional. Untuk mengetahui interpretasi yang tepat dari prinsip kedaulatan, artikel ini menggunakan metode kualitatif. Studi ini menemukan bahwa kedaulatan diakui sebagai salah satu prinsip dalam pengakuan suatu negara. Istilah ini bernuansa politis, karena aspek pengakuan itu sendiri bukanlah aspek hukum melainkan aspek politik. Apalagi, dalam beberapa kasus, meski suatu negara telah memproklamasikan kedaulatannya, masih ada peluang bagi sebagian wilayahnya untuk merdeka atau bahkan diakuisisi oleh negara lain. Dengan demikian, nampaknya prinsip kedaulatan memiliki kecenderungan sebagai bagian dari politik. Namun asas kedaulatan tetap merupakan asas hukum berdasarkan ketentuan hukum internasional, dimana setiap negara memiliki hak eksklusif di setiap bagian wilayahnya, yaitu di darat, udara dan laut. Saat ini, konsep hukum internasional telah merambah ke politik kajian hukum internasional, dimana berbagai aspek penegakan hukum berbaur dengan kebijakan suatu negara yang identik dengan aspek politik. Oleh karena itu, disimpulkan bahwa asas kedaulatan yang berlaku saat ini harus dilengkapi dengan asas hukum lain dalam hukum internasional.